Durability of tiled-wall and composite system under differential movement (phase I and II) - Guan, Lingwei (2008)
After a series of falling-tile incidents, the entire process of external wall tiling in Singapore needs to be reviewed and investigated. However, most studies on the tiled wall performance don?t consider the impacts of combined elements in Singapore?s tropical climate or conduct transit thermal analysis. This study will account for these considerations through experimental tests and numerical modelling. The experimental model consisted of a series of layered composite specimens, designed and fabricated by fixing different tiles on concrete slabs with various fixatives. These specimens were subjected to accelerated weathering tests after curing, and then tested destructively with chosen yardsticks of pull-off and shear-off strengths, together with the critical displacement corresponding to the commencement of tile?s break off. On the other hand, in order to overcome the limitation of the laboratory tests, numerical modelling is employed to analyse the influence of thermal effects and of the physical factors. The numerical model is based on a typical non-load bearing tiled wall and a typical tropical climate condition as in Singapore. After a case study, parametric analyses were conducted to study the impact of top grout, fixative materials and the distribution of the shear stress around the top area.